The influence of norms and values on the provision of termination of pregnancy services in South Africa. (2017) - Röhrs, Stefanie
Abstract: Introduction: As front-line providers, nurses play an integral role in the implementation of South Africa's Choice on Termination of Pregnancy Act and, thus, the promotion of women's reproductive rights. In light of low levels of support for termination of pregnancy services in South Africa, it is important to understand nurses' views of such services. The purpose of this study was to examine how nurses' norms and values shape the provision of abortion services. Methods: Qualitative interviews with nurses were conducted at seven rural hospitals in the Western Cape Province of South Africa. Data were analysed using thematic and narrative analysis. Results: Nurses, like other public service workers, make moral judgments about their clients. They classify clients seeking abortions into two groups: those 'worthy' of support, and those 'unworthy' of support. Nurses' moral judgments are largely shaped by the circumstances of the pregnancy and the behaviour of the client. In addition, nurses' understanding of their professional identity and their work environments may influence their decision whether a client deserves their assistance. While nurses claimed that they would offer the same services to all of their clients, further research on the availability and quality of abortion services is required to confirm these results. Conclusion: The study shows that nurses make moral judgments about abortion clients and divide them into deserving and less deserving clients. These value judgments undermine the rights-based approach of South African legislation, which provides every women with the right to choose whether they wish to terminate a pregnancy.